Construction for landscape architecture - Holden, Robert, 1947-; Liversedge, Jamie (London : Laurence King Pub., 2011)
Construction for Landscape Architecture covers all aspects of landscape construction, giving a good understanding of building materials and assembly. It is heavily illustrated with specially commissioned, detailed construction drawings, and has a strong emphasis on sustainability and good practice. At the end of the book there is an extensive glossary and an appendix of technical information.
Construction for Landscape Architecture; Contents; Introduction; The vernacular tradition and globalization; Sustainability; Attitudes to materials; A note on standards; About this book; General principles; Properties of materials; Specific gravity; Size; Strength; Optical characteristics; Electrical conductivity; Color and texture; Thermal properties; Acoustic properties; Deformation; Principles of assembly; Loads and reactions; Building Materials; Stone; Igneous rocks; Sedimentary rocks; Metamorphic stone; Stone finishes and forms; Concrete; Strength classes Step by step: Constructing a curved cast-in-place concrete retaining wallWaterproof concrete; Ecoconcrete; Photocatalytic (depolluting) concrete; Reinforced concrete; Step by step: Constructing GRC rockwork; Concrete finishes; Stucco; Harling; Brick; Materials used in making bricks; Process of manufacture; Types of brick; The brick-wall bond; Paving bonds; Mortar; Jointing and pointing; Laying paving; Problems with brickwork; Step by step: Constructing an engineering-brick retaining wall; Metals; Forming and working metals; Iron; Cast iron; Wrought iron; Steel; Aluminum; Copper; Zinc; Lead AlloysLumber; Types of lumber; Step by step: Constructing hardwood lumber decking; Sustainability of lumber; Strength; Moisture content and seasoning; Durability and ease of preservation; Glass; Modern manufacture; Applications in external works; Polymers (plastics and rubber); Manufacturing and applications; Elastomers: rubber and synthetic rubber; Toxicity and health concerns associatedwith plastics and elastomers; Environmental concerns; Polymer degradation; Earth, turf, and non-conventional materials; Compressed earth, cob, and pisé; Turf and peat walls; Elements Earthworks and topsoil in relation to structuresTopsoil; Groundwater; Protection of trees; Bearing capacity of soil; Cut and fill; Drainage; Mounds and landfill; Topsoil grading; Step by step: Forming a berm using clay subsoil; Retaining structures; Steps; Ramps and ramped steps; Introduction to retaining walls; Cantilever walls; Piled walls; Anchored walls ("tieback" walls); The ha-ha; Soil reinforcement; Geotextiles as soil reinforcement; Walls; Materials used in wall construction; Design issues; Unit walls; Foundations and structure; Moisture-proof courses; Expansion joints; Drystone walls Drystone wall typesPaving; Foundations; Rigid paving; Step by step: Rigid paving; Unit paving; Flexible paving; Edge restraint; Color in paving; Porous paving; Drainage; Design of paving; Step by step: Flexible herringbone paving; Dealing with water; Introduction to pool construction; Informal pools and rigid structures; Step by step: Building a rigid pool; Step by step: Building a flexibly lined pool; Ponds, pools, lakes, canals, basins, and rills; Step by step: Constructing a rigid channel; Cascades, waterfalls, and weirs; Assembly; Fasteners and connections; Lumber fixings
Includes bibliographical references (p. 222-224) and index.
Keywords: Landscape architecture